Utilizing TikTok as a means of self-actualization for students at SLB Negeri 1 Sleman - Oktaviani, Riski Putri; Aprilia, Monika Pretty (Privietlab, 2026)
This study aims to describe the form of self-actualization of students at SLB N 1 Sleman in creating content on the TikTok account @slbn1sleman. This study used a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation and analyzed using Gerald Millerson's media production theory and Alfred Schutz's phenomenological approach. The results show that student actualization occurs in three stages: pre-production, production, and post-production. The pre-production stage includes planning content ideas from daily activities, production involves students, actors, and teacher guidance, and post-production includes simple editing and evaluation. The content functions as an educational medium that can change public perceptions of children with special needs. A supportive school environment is a major factor. This study is expected to serve as a reference for other special needs schools in using social media for student education and empowerment.